Pengembangan Game Bergenre Tower Defense Dengan Mengimplementasikan Augmented Reality - Galih Muhammad; Wibisono Sukmo Wardhono; Issa Arwani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Game development by implementing the Augmented Reality has a profound effect on the gameplay aspects of the user experience on the game itself. This paper describes the development of the game Omega Defender with the primary objective as the research and development of mobile games which implement Augmented Reality, with an image as a marker. The goal of the game omega Defender is survive to the end level of the game without dying, destroy all the enemies that appear on the screen by detecting a marker at the start of the game. Augmented Reality will enhance the user experience by improving the user interaction with the real world. The design of the game itself begins from the selection of the conceptual framework will be used, in this study, MDA framework used as an appropriate concept to develop the game Omega Defender. Paper prototyping is done as the first step of development, followed by digital prototyping to implement all the elements that exist in paper prototyping and modify it to fit the digital game. Omega defender has been tested with multiple users to evaluate the results of the development of the game itself. In the process of Play testing obtained two analyzes based on user feedback that is, 2 factors fun and 4 factors not fun from Omega Defender game.